TORSION OF APPENDIX OF TESTIS - Rashid, Muhammad Misbah; Murtaza, Badar; Khan, Naser Ali (Journal of Ayub Medical College Abbottabad, 2007)
An case of torsion of the appendix of testis is described in a 10 years old boy. He presented with sudden onset of severe pain in the left testis of 3 days duration. Emergency exploration of the left testis revealed a gangrenous appendix of the left testis. The appendix of the testis was excised and the wound was closed. The patient made a smooth post-operative recovery. KEY WORDS: torsion, appendix testis, exploration, gangrene